Autistes : entre situations de vulnérabilité et pouvoir d’agir ? - Julie Dumonteil (Éducation et Socialisation)
Autistic people are discriminated against in their access to education, schooling and vocational training. The European Committee of Social Rights recently condemned France for this reason. If autistic people often experience persecution and victimization, it is because autistic spectrum traits express themselves at the field, which build the heart of the social environment, interpersonal relationships. Collectiveness is vital for human beings because of their fundamental vulnerability related to their own limitations. But do autistic people constitute a particularly vulnerable group? Or do they find themselves in situations that increase vulnerability? Or do their life-experiences generate increased vulnerability? After focusing on an anthropological definition of the notion of vulnerability, the phenomena of vulnerabilization of autistic people is analyzed to understand how education can fight it by encouraging autistic empowerment.